2008
DOI: 10.3855/jidc.279
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance of Salmonella enterica serovars Typhi and Typhimurium isolated from clinical samples at two rural hospitals in Western Kenya

Abstract: Background: The threat to human health posed by antibiotic resistance is of growing concern. Many commensals and pathogenic organisms have developed resistance to well established and newer antibiotics. This is a cross-sectional study within two hospital settings to determine in vitro antibiotic susceptibilities of Salmonella species isolated in blood, cerebral spinal fluid, pus and stool collected from in-and out-patients. The inclusion criteria was non restrictive to in-and out-patient but preference to seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Our study is the same as shown by shymapada et al, [13] who found that chloramphenicol was the most active and usually used drug for typhoid fever is most broadly used anti-microbial agents. The action by "inhibiting bacterial enzymes DNA gyrase" which is responsible for coiling, division and super coiling of bacteria lDNA during reproduction from present study showed all strain of local S. typhi were resistance for gentamycin as shown by results of aacC2 gene and this results as like mentioned by onyango et al ., [14] who said that Reference to amino glycosides resistance amplification was detected for aacC2 gene, mechanism of antibiotic resistance in S.typhi is refereed by two aspects This first acquisition of foreign genes by plasmids and mutation on chromosome,resistance can be attained by horizontal acquisition of resistance-genes, mobilized by conjugative plasmids, insertion sequences and transposons, by "recombination of foreign-plasmids DNA into the chromosome or by mutations in different chromosomal loci". Consistent with the reported of Randall et al, [15] there was numerous instance in this study when an isolate was resistant to an anti-microbial drug, but the characteristics of the gene conferring resistance was not ascribed with the primers used in the study.…”
Section: Resultsmentioning
confidence: 99%
“…Our study is the same as shown by shymapada et al, [13] who found that chloramphenicol was the most active and usually used drug for typhoid fever is most broadly used anti-microbial agents. The action by "inhibiting bacterial enzymes DNA gyrase" which is responsible for coiling, division and super coiling of bacteria lDNA during reproduction from present study showed all strain of local S. typhi were resistance for gentamycin as shown by results of aacC2 gene and this results as like mentioned by onyango et al ., [14] who said that Reference to amino glycosides resistance amplification was detected for aacC2 gene, mechanism of antibiotic resistance in S.typhi is refereed by two aspects This first acquisition of foreign genes by plasmids and mutation on chromosome,resistance can be attained by horizontal acquisition of resistance-genes, mobilized by conjugative plasmids, insertion sequences and transposons, by "recombination of foreign-plasmids DNA into the chromosome or by mutations in different chromosomal loci". Consistent with the reported of Randall et al, [15] there was numerous instance in this study when an isolate was resistant to an anti-microbial drug, but the characteristics of the gene conferring resistance was not ascribed with the primers used in the study.…”
Section: Resultsmentioning
confidence: 99%
“…Resistant strains have also been observed in Kenya with resistance against cotrimoxazole in 66.7% (22 individuals) of the S . Typhi clinical isolates (Onyango et al, 2008) and in the United States where sulfamethoxazole resistance was observed in 56% of food-borne S . Typhi isolates (Glynn et al, 2004).…”
Section: Introductionmentioning
confidence: 99%